Probative reasoning based on indications - Zavaleta Rodríguez, Roger E. (2018)
In this article, the author analyzes the assessment of the evidence within the evidentiary reasoning, developing the concept of evidence, its importance in the process, its classification and evaluating its usefulness according to the criteria of correction of the judicial presumption.